1989
DOI: 10.1177/014860718901300199
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Breakage of a Totally Implanted Venous Access System

Abstract: Totally implantable systems for venous access are now in wide clinical use. They have been shown to have several advantages when compared with earlier systems. However, the advantages of total implantation also contain risks for new complications. In situ breakages may have disastrous results when unnoticed. In situ separations have been reported with systems consisting of a separate reservoir and catheter. A case is reported where in situ breakage occurred in a system with prefixed catheter. The catheter migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…9 Catheter fracture and migration could be a result of many surgical and non-surgical factors; however, it is usually difficult to identify the exact aetiology. 27 Surgical factors include poor connection of the catheter to the port, damage of the catheter during assembly at the site of anastomosis, 16,27,28 and improper positioning of the catheter. 11,[29][30][31] Non-surgical factors include forced flushing, vigorous movements of upper extremities, neck flexion, congestive heart failure, increasing in thoracic pressure with coughing and vomiting, and catheter damage by chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Catheter fracture and migration could be a result of many surgical and non-surgical factors; however, it is usually difficult to identify the exact aetiology. 27 Surgical factors include poor connection of the catheter to the port, damage of the catheter during assembly at the site of anastomosis, 16,27,28 and improper positioning of the catheter. 11,[29][30][31] Non-surgical factors include forced flushing, vigorous movements of upper extremities, neck flexion, congestive heart failure, increasing in thoracic pressure with coughing and vomiting, and catheter damage by chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of catheter dislodgment are related to surgical and non-surgical factors. The former include poor connection of the catheter to the port, or inappropriate application of the plastic catheter lock, catheter damage at the site of anastomosis during assembly (18)(19)(20), improper catheter positioning (3,(21)(22)(23). The latter include forced flushing, upper extremity vigorous movements, neck flexion, congestive heart failure, changing in thoracic pressure with coughing and vomiting, catheter damage by chemotherapic drugs, and the so called "pinch-off syndrome" (14,(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Few reports of catheter damage that inadvertently occurs prior to device insertion have been published (Kirvela & Satokari, 1989;Liu et al, 2004), but it has been observed in clinical practice. This type of catheter damage is believed to occur more often than it has been documented in the literature (Montreuil, 2004).…”
Section: An Unusual Cause Of Shoulder Painmentioning
confidence: 99%